Changing Gears – DBS For Dopaminergic Desensitization in Parkinson's Disease?. Issue 5 (20th July 2021) - Weiss, Daniel; Volkmann, Jens; Fasano, Alfonso; Kühn, Andrea; Krack, Paul; Deuschl, Günther
Abstract : In Parkinson's disease, both motor and neuropsychiatric complications unfold as a consequence of both incremental striatal dopaminergic denervation and intensifying long‐term dopaminergic treatment. Together, this leads to 'dopaminergic sensitization' steadily increasing motor and behavioral responses to dopaminergic medication that result in the detrimental sequalae of long‐term dopaminergic treatment. We review the clinical presentations of 'dopaminergic sensitization', including rebound off and dyskinesia in the motor domain, and neuropsychiatric fluctuations and behavioral addictions with impulse control disorders and dopamine dysregulation syndrome in the neuropsychiatric domain. We summarize state‐of‐the‐art deep brain stimulation, and show that STN‐DBS allows dopaminergic medication to be tapered, thus supporting dopaminergic desensitization. In this framework, we develop our integrated debatable viewpoint of "changing gears", that is we suggest rethinking earlier use of subthalamic nucleus deep brain stimulation, when the first clinical signs of dopaminergic motor or neuropsychiatric complications emerge over the steadily progressive disease course. In this sense, subthalamic deep brain stimulation may help reduce longitudinal motor and neuropsychiatric symptom expression – importantly, not by neuroprotection but by supporting dopaminergic desensitization through postoperative medication reduction. Therefore, we suggest considering STN‐DBS early enough before patients encounter potentially irreversible psychosocial consequences of dopaminergic complications, but importantly not before a patient shows first clinical signs of dopaminergic complications. We propose to consider neuropsychiatric dopaminergic complications as a new inclusion criterion in addition to established motor criteria, but this concept will require validation in future clinical trials. ANN NEUROL 2021;90:699–710